A pilot plant scale testing of the application of seaweed-based natural coating and modified atmosphere packaging for shelf-life extension of fresh-cut apple - Augusto, Ana (2022)
Codium tomentosum hydroethanolic extract was obtained using a pilot solid–liquid extractor to validate the anti-browning functionality of the extract under industrial conditions. Fresh-cut apple slices were coated by immersion in: (1) a seaweed extract solution (0.5% w/v) and (2) a commercial coating, and the two sets of samples were compared with a control (immersion in water). Packaged samples were stored, under ambient and modified atmosphere conditions at 4°C. After 30 days of storage, the samples that were coated with the seaweed extract and packaged under modified atmosphere, demonstrated lower peroxidase activity and polyphenol oxidation when compared with the samples treated with the commercial additive. These results confirm, at pilot scale and under industrial production conditions, the efficacy of the seaweed extract as a bio-based substitute for the synthetic coatings, which are currently used to prevent browning in fresh-cut apples. Novelty impact statement Fresh-cut fruits are subjected to processing operations leading to a decrease in nutritional and organoleptic properties. It is therefore necessary to adopt strategies to delay the degradative processes. In this study, the efficacy of a pilot-scale production and industrial application of a coating formulated with Codium tomentosum seaweed extract has been established for the first time. This seaweed extract possesses the potential to prevent browning development in fresh-cut apples under industrial operating conditions.